A Cross-Linked Triphenylamine-Based Polymer Cathode Material with Dual Anion-Cation Reversible Insertion for Lithium Ion Battery. Issue 12 (1st January 2019) - Chen, Sha; Jia, Tao; Zhou, Guangying; Zhang, Chengjun; Hou, Qiong; Wang, Yuhai; Luo, Suilian; Shi, Guang; Zeng, Yonghua
Abstract : A cross-linked triphenylamine polymer poly[N, N'-bis(4-diphenylaminophenyl) naphthalene-1, 4, 5, 8-tetracarboxylic diimide] cathode material with dual anion-cation reversible insertion is polymerized from monomer N, N'-bis(4-diphenylaminophenyl) naphthalene-1, 4, 5, 8-tetracarboxylic diimide by chemical oxidative polymerization, which has a very low solubility in common organic solvents and electrolytes. The triphenylamine unit in the polymer can reversibly dope/dedope the PF6 − anion, while the naphthalimide unit can reversibly insert/extract the lithium cation. The lithium ion half-cells with the polymer as a cathode and the lithium foil as an anode are assembled and the electrochemical properties are tested. For comparison, the electrochemical properties of monomer are studied. Thanks to its cross-linked network structure, the electrochemical performance of polymer is much better than that of its monomer. The polymer has excellent cycle performance, the initial discharge specific capacity is 140 mAh g −1, which is close to its theoretical specific capacity, and the capacity can still be maintained at 125 mAh g −1 after 100 cycles, suggesting that this polymer is a potential cathode material for lithium ion batteries.